Bond Strength of a Diatomic Acceptor Ligand: A Reliable Measure of Its Antibond Occupation and Its Charge?. Issue 32 (14th September 2022) - Popp, Jens; Klüfers, Peter
Abstract: A nitrosyl ligand is bonded to a central metal mainly via a mostly covalent normal bond and a coordinative metal‐to‐NO π‐backbond. A recent analysis had unravelled similar bonding characteristics of both linear and bent CoNO moieties in terms of ligand charge and antibond occupation. Thus, there should be no justification for the usual assignment of an NO + ligand to a linear MNO unit and a singlet‐NO − ligand to a bent one. This claim seems to contradict that bending an MNO unit weakens the N−O bond with a marked red‐shift of the N−O stretch as one indicator. In this work, the failure of Dewar‐Chatt‐Duncanson‐derived conclusions is demonstrated for linear/bent isomer couples by the analysis of M−N and N−O bond strengths. Instead of DCD behavior, lateral electrostatic influence on NO and other diatomic ligands modulates the intraligand bond strength in a similar way as has been shown in former work for polar interaction of a charge with CO in the 'non‐classical' carbonyls. Methodologically, local‐mode analysis is used to determine bond strengths. Oxidation states are determined by the effective‐oxidation‐state (EOS) method. Abstract : Cobalt(II) precursors react with NO to bent Co−N−O functions mostly. When compared with linear functions, they exhibit a red‐shift of the N−O stretch by about 200 cm −1 . Bent‐bonded nitrosyls thus are seen as NO − and linearly bonded ones as NO + . However, the expected charge differences are not verified by computation–leaving the origin of the red‐shift unclear. We tackle the problem by looking at the peculiarities of lateral bonding of a diatomic.